A case against transformational leadership: Empirical examples from political history of South Asia. Issue 3 (14th August 2017) - Yousaf, Nadeem
Abstract : Purpose: Transformational and transactional leadership have become a fascinating issue for research since the work of Burns (1978) and Bass (1990). The purpose of this paper is to evaluate the usefulness of the concept of transformational leadership using examples of political leadership from South Asia. It is argued that the construct of transformational leadership is practically non-existent. And, if the concept of transformational leadership exists, it cannot be specifically applied to the leaders who gain popularity and achieve their goals. It is also argued that positive and negative connotation with transformational and transactional leadership, respectively, is false. The popular leadership may be good for "one-point agenda, " but not necessarily transform the system. Design/methodology/approach: Qualitative methods, historical analysis, and discourse analysis have been employed to understand the leaders' actions and behaviors. Findings: The discussion around the empirical examples show that the popular-successful leadership does not necessarily a transformational leadership even though the leadership achieves the goals. Originality/value: The popular or so-called transformational leadership may be good to achieve one-point agenda, but it may not bring the required change and fruitful results to all stakeholders if it is not backed by a transactional strategy. Future research may turn the attention in three directions: whether or not the achieved goals were transformational or transactional; evaluation of leaders' behavior from the perspective of consequential leadership; and the role of transactional leaders in the growth and strengthening of micro and macro organizations.